Two-dimensional non-LTE O I 777 nm line formation in radiation hydrodynamics simulations of Cepheid atmospheres - Vasilyev, Valeriy; Ludwig, Hans-Günter; Lemasle, Bertrand (Astronomy and astrophysics, 2019)
Oxygen abundance measurements are important for understanding stellar structure and evolution. Measured in Cepheids, they further provide clues on the metallicity gradient and chemo-dynamical evolution in the Galaxy. However, most of the abundance analyses of Cepheids to date have been based on one-dimensional (1D) hydrostatic model atmospheres. Here, we test the validity of this approach for the key oxygen abundance diagnostic, the O I 777 nm triplet lines. We carry out two-dimensional (2D) non-LTE radiative transfer calculations across two different 2D radiation hydrodynamics simulations of Cepheid atmospheres, having stellar parameters of Teff = 5600 K, solar chemical compositions, and log g = 1.5 and 2.0, corresponding to pulsation periods of 9 and 3 days, respectively. We find that the 2D non-LTE versus 1D LTE abundance differences range from −1.0 to −0.25 dex depending on pulsational phase. The 2D non-LTE versus 1D non-LTE abundance differences range from −0.2 to 0.8 dex. The abundance differences are smallest when the Cepheid atmospheres are closest to hydrostatic equilibrium, corresponding to phases of around 0.3–0.8, and we recommend these phases for observers deriving the oxygen abundance from O I 777 nm triplet with 1D hydrostatic models.
Gesehen am 13.05.2019